Characteristical analysis of tidal and residual currents in the sea area around Tangshan international tourism island. Issue 2 (January 2021) - Yang, Jinzhi; Ding, Wenping; Cui, Jiaxing; Guo, Shan
Abstract: For the sea area around Tangshan international tourism island, continuous conservation of ocean current at 3 stations were carried out. The harmonic analysis was conducted based on the measured data. According to the harmonic analysis results, the flow velocity, type, movement form of tidal current and residual current distribution were researched finely. The results show that the sea area was dominated by regular semi-diurnal tidal currents. The movement form of tidal current was reciprocating current, and the trend of residual current presented regional differences. The research had an important practical significance for the resource development and marine engineering construction of the sea area.